Der gerettete Retter: Exodus 1-2 in patristischer und rabbinischer Interpretation - Siquans, Agnethe (2021)
The book deals with patristic and rabbinic interpretations of the birth story of Moses in Exodus 1-2. The Christian and Jewish exegetes of late antiquity interpreted the text as part of their Bible, in dialogue with each other and in dissociation from each other.